Impact of Design Changes in Gastrostomy Tube (G-tube) Devices for Patients Who Rely on Home-Based Blenderized Diets for Enteral Nutrition. (19th May 2019) - Guha, Suvajyoti; Bouhrira, Nesrine; Antonino, Mark J.; Silverstein, Joshua S.; Cooper, Jeffrey; Myers, Matthew R.
Abstract: Objective: Blenderized diets are gaining increasing popularity among enteral tube users. Connectors in gastrostomy tubes (G-tubes) are undergoing standardization to reduce misconnections. These standardized G-tubes are referred to as ENFit G-tubes. This study was performed to quantify the in vitro performance of existing (legacy) G-tubes and compare them with ENFit G-tubes for blenderized diets. Method: Patient blenderized diet recipes and practices were obtained through patient advocacy groups. Different blenders and blending times were studied. Five legacy G-tube brands and three corresponding ENFit brands, sized between 14 Fr and 24 Fr, were studied under gravity and push modes of feeding. Results: Considering both thin and thick blenderized gravity mode diets, an average increase in feeding time from 20 minutes to 32 ± 18 minutes in transitioning from legacy to ENFit was observed with standard G-tubes, compared to 22 ± 3.5 minutes for low profiles. For push-mode diets, a 60-second push with standard ENFit G-tubes was easier compared to standard legacy G-tubes (61% ± 21% as much force), but faster 5-second pushes required considerably more effort for ENFit standard G-tubes (167% ± 96%). Low-profile ENFit G-tubes required slightly less effort compared to low-profile legacies for both 60-second and 5-second pushes (72% ± 22% and 90% ± 19%, respectively). Clogging was common in both legacy and ENFit devices, particularly under gravity mode. Conclusions: For a push mode of feeding, patients will largely be unimpacted after the transition to ENFit. For a gravity mode of feeding, some ENFit users may need higher-powered blenders and should expect increased feeding times.